Collaboration and technology : 22nd International Conference, CRIWG 2016, Kanazawa, Japan, September 14-16, 2016, Proceedings /: 22nd International Conference, CRIWG 2016, Kanazawa, Japan, September 14-16, 2016, Proceedings. (2016) - Unknown
No abstract available